2009
DOI: 10.1074/mcp.m900195-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse C2C12 Myoblast Cell Surface N-Linked Glycoproteome

Abstract: Endogenous regeneration and repair mechanisms are responsible for replacing dead and damaged cells to maintain or enhance tissue and organ function, and one of the best examples of endogenous repair mechanisms involves skeletal muscle. Although the molecular mechanisms that regulate the differentiation of satellite cells and myoblasts toward myofibers are not fully understood, cell surface proteins that sense and respond to their environment play an important role. The cell surface capturing technology was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 119 publications
1
32
0
Order By: Relevance
“…The Ig superfamily members CD 166 and CD 276, which were up-regulated in our microarray, have also been detected at the surface of mouse C2C12 myoblasts [33], suggesting a role for these two proteins in early myoblast-myoblast interactions. Other membrane proteins that were both up-regulated in superficial hyperplastic zones in our study and that have been detected at the surface of C2C12 cells included cleft lip and palate transmembrane protein1, trophoblast glycoprotein, tissue factor/CD142, Ephrin type A receptor 2, tetraspanin 3 and 4 and fibroblast growth factor 4 (FGFR4) [33]. FGFR4 is highly expressed during chick embryo muscle differentiation [34] (Marics et al, 2002) and muscle regeneration [35].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The Ig superfamily members CD 166 and CD 276, which were up-regulated in our microarray, have also been detected at the surface of mouse C2C12 myoblasts [33], suggesting a role for these two proteins in early myoblast-myoblast interactions. Other membrane proteins that were both up-regulated in superficial hyperplastic zones in our study and that have been detected at the surface of C2C12 cells included cleft lip and palate transmembrane protein1, trophoblast glycoprotein, tissue factor/CD142, Ephrin type A receptor 2, tetraspanin 3 and 4 and fibroblast growth factor 4 (FGFR4) [33]. FGFR4 is highly expressed during chick embryo muscle differentiation [34] (Marics et al, 2002) and muscle regeneration [35].…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, we found that Junctional adhesion molecule Jam2b which is closely related to jam2a (Jam-B) and Jam3b (JAM-C), both critical for myocyte fusion [32], was also up-regulated along with protogenin which is closely related to the promyogenic transmembrane protein Neogenin [30]. The Ig superfamily members CD 166 and CD 276, which were up-regulated in our microarray, have also been detected at the surface of mouse C2C12 myoblasts [33], suggesting a role for these two proteins in early myoblast-myoblast interactions. Other membrane proteins that were both up-regulated in superficial hyperplastic zones in our study and that have been detected at the surface of C2C12 cells included cleft lip and palate transmembrane protein1, trophoblast glycoprotein, tissue factor/CD142, Ephrin type A receptor 2, tetraspanin 3 and 4 and fibroblast growth factor 4 (FGFR4) [33].…”
Section: Discussionmentioning
confidence: 99%
“…23, 24 Itfg3 is a single pass transmembrane protein with confirmation as a glycoprotein. 25, 26 Serpinb6b is a member of the widely studied serine protease inhibitor family, the serpins, that inhibit their enzyme targets by covalent modification, an activity that is consequential to numerous and widespread biological processes. 27 Adseverin belongs to the villin superfamily of proteins, which function in actin remodeling in response to calcium signaling.…”
Section: Discussionmentioning
confidence: 99%
“…CSC technology has also been applied to mouse myoblast cells, mouse β -cells, hepatoma cells, leukemia cells, pluripotent stem cells, Drosophila Kc167 cells, and neuronal progenitor cells. 145,156163 Recently, Wollscheid and co-workers used CSC technology to identify cell-surface proteins in 41 human and 31 mouse cell lines. 164 This work is summarized in a publically available resource: the Cell Surface Protein Atlas (CSPA).…”
Section: Enrichment Of Glycoproteins and Glycopeptidesmentioning
confidence: 99%